Product Evaluation and Travel Motivation of Domestic Tourists to Island Destinations in Malaysia. (Global Business Management Review (GBMR), 2014)
This study focuses on product evaluation and tested the relationship between the pull and the push aspects of travel motivation theorized by Dann, (1981) and McGee et al. (1996) within the context of domestic tourism in island destinations. Thus it offers an original contribution to the literature. The study uses personally assisted quantitative survey method at major entry and exit points to four island destinations in the northwest of Peninsular Malaysia. Domestic tourists spending at least one night at the destinations were the study’s respondents. Product evaluation findings showed that domestic tourists are concerned with having a wider range of accommodations, an improvement the quantity of the public transport, and a wider range of pricing to suit their needs. They are only moderately impressed with the quality of accommodation, transportation, attractions, and activities provided at the island destinations and are least impressed with the prices, mobile and internet connection as well as food/beverage outlets location and food presentations. Test on the relationship between the pull and push aspects of travel motivation indicated a strong link between the tested variables, thereby providing empirical proof to the tested theory. The practical implication was that destination managers should focus more on quality of tourism provision instead of quantity.